Interhemispheric Cortical Inhibition Is Reduced in Young Adults With Developmental Coordination Disorder - He, Jason L.; Fuelscher, Ian; Enticott, Peter G.; Teo, Wei-peng; Barhoun, Pamela; Hyde, Christian (Frontiers in Neurology, 2018)
Introduction: While the aetiology of Developmental Coordination Disorder (DCD) is yet to be established, brain-behavior modelling provides a cogent argument that neuropathology may subserve the motor difficulties typical of DCD. We argue that a number of the core behavioral features of the DCD profile (such as poor surround inhibition, compromised motor inhibition and the presence of mirror movements) are consistent with difficulties regulating inhibition within the primary motor cortex (M1). This study aimed to be the first account of the integrity of cortical inhibition in motor cortices in DCD. Method: The sample consisted of eight adults with DCD aged (18 to 30 years) and 10 aged matched neurotypical controls. Participants received a common battery of single and paired-pulse transcranial magnetic stimulation (TMS) from which a series of neurophysiological measures classically used to measure intra (e.g., short-interval cortical inhibition [SICI], long-interval cortical inhibition [LICI] and cortical silent period [CSP]) and inter (e.g., ipsilateral silent period [ISP]) hemispheric cortical inhibition of the M1 at rest were recorded. Results: While no group differences were observed for any measure of intrahemispheric cortical inhibition, individuals with DCD demonstrated significantly reduced interhemispheric cortical inhibition relative to controls, shown by consistently lower ISPratios. Conclusion: Our findings are consistent with the view that regulation of cortical inhibition of M1 activity may be atypical in individuals with DCD, indicating differential GABAergic operation. This effect, however, appears to select to interhemispheric cortical inhibition. Importantly, our data support the view that reduced interhemispheric M1cortical inhibition may at least partly explain commonly reported difficulties with bimanual motor control in DCD. The neurochemical implications and limitations of this evidence will be discussed.